2016
DOI: 10.5649/jjphcs.42.78
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Intervention to Manage Polypharmacy in Elderly Patients based on STOPP Criteria

Abstract: Polypharmacy, the co-prescribing of nonessential drugs and inappropriate prescriptions, is a worldwide issue and is a factor affecting the increase in adverse drug reactions, drug-drug and drug-disease state interactions, and the growth in medical spending. In this study, we evaluated the current status of polypharmacy in elderly patients at Kobe University Hospital and the efficacy for screening and intervention against potentially inappropriate medications (PIMs) with the screening tool of older persons' pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In Japan, the “Screening Tool for Older Persons’ Appropriate Prescriptions for Japanese (STOPP-J) [8]” is used. The use of drugs related to the Beers or STOPP criteria and the consequent under-prescribing of medications were reported to be frequent in patients receiving multidrug treatment [911]; similar reports were also published in Japan [12, 13]. We hypothesize that adverse events tend to occur in patients receiving multidrug treatment because of high-risk prescriptions.…”
Section: Introductionmentioning
confidence: 72%
“…In Japan, the “Screening Tool for Older Persons’ Appropriate Prescriptions for Japanese (STOPP-J) [8]” is used. The use of drugs related to the Beers or STOPP criteria and the consequent under-prescribing of medications were reported to be frequent in patients receiving multidrug treatment [911]; similar reports were also published in Japan [12, 13]. We hypothesize that adverse events tend to occur in patients receiving multidrug treatment because of high-risk prescriptions.…”
Section: Introductionmentioning
confidence: 72%
“…For example, Imai et al, reported that the service prevents potential adverse drug reactions [9] and Horiuchi et al, reported that screening of cancellation medicine before operation at medicine support center [13]. The CPBM is necessary to evaluate patients' pharmacotherapy and pharmacists could work for the risk management using STOPP criteria [14][15][16]. In the NCCHE, pharmacists do not use STOPP criteria [14] for inpatient intervention, however, the change of work setting was associated with a twofold increase in pharmacy interventions for patients' treatment.…”
Section: Discussionmentioning
confidence: 99%